"Like Recycles Like": Selective Ring‐Closing Depolymerization of Poly(L‐Lactic Acid) to L‐Lactide. (9th June 2022) - Cederholm, Linnea; Wohlert, Jakob; Olsén, Peter; Hakkarainen, Minna; Odelius, Karin
Abstract: Chemical recycling of poly(L‐lactic acid) to the cyclic monomer L‐lactide is hampered by low selectivity and by epimerization and elimination reactions, impeding its use on a large scale. The high number of side reactions originates from the high ceiling temperature ( T c ) of L‐lactide, which necessitates high temperatures or multistep reactions to achieve recycling to L‐lactide. To circumvent this issue, we utilized the impact of solvent interactions on the monomer–polymer equilibrium to decrease the T c of L‐lactide. Analyzing the observed T c in different solvents in relation to their Hildebrand solubility parameter revealed a "like recycles like" relationship. The decreased T c, obtained by selecting solvents that interact strongly with the monomer (dimethyl formamide or the green solvent γ‐valerolactone), allowed chemical recycling of high‐molecular‐weight poly(L‐lactic acid) directly to L‐lactide, within 1–4 h at 140 °C, with >95 % conversion and 98–99 % selectivity. Recycled L‐lactide was isolated and repolymerized with high control over molecular weight and dispersity, closing the polymer loop. Abstract : A novel approach is taken to decrease the ceiling temperature of L‐lactide, enabling chemical recycling of high molecular weight poly(L‐lactic acid) directly back to the cyclic lactide monomer (CRM) with high selectivity. By utilizing specific solvent interactions, the CRM can be performed at a moderate temperature; thereby, obstructing side reactions are diminished.